Zika in gestation. Impact on execution skills and maturity age in infants - Hernádez Vergel, Viviana Karina; Prada Núñez, Raúl; Hernández Suárez, César Augusto (Revista Cuidarte, 2022)
Introduction: Zika virus is transmitted through the bite of infected mosquitoes, but it can also occur through an intrauterine infection before delivery, and the virus passes to the fetus. Objective: describe the level of impairment in performance skills and maturation age of brave boys and girls of the future program with neonatal Zika virus infection. Materials and Methods: Research is framed with a quantitative correlational approach supported by field research and non-experimental design, with a sample of 15 infants aged 3, 4 and 5 years. The data collection technique used was the Abbreviated Scale. Results: Regarding the areas evaluated with respect to maturational age, it was found that the weighting of motor skills and praxis found a correlation coefficient of 0.601 (moderate) and in the sample of performance skills of 3-year-old children. With gestational zika, a correlation of 0.853 (strong) was obtained. Discussion: Zika virus infection in boys and girls, acquired during pregnancy, strongly limits the execution skills typical of maturational age in this population. Conclusions: there is a correlation between infants with gestational zika and strong involvement in the actions or behaviors that a patient has in moving and physically interacting with activities, objects and thus performing a learned motor activity. How to cite this article: Hernández Vergel Viviana Karina, Prada Núñez Raúl, Hernández Suárez César Augusto. Zika en la gestación. Afectación de las destrezas de ejecución y edad madurativa en infantes. Revista Cuidarte. 2022;13(2):e1928. http://dx.doi.org/10.15649/cuidarte.1928